SEMANTIC ESSENCE OF QUALITY PREDICATES IN THE STRUCTURE OF A COMPOUND SENTENCE - Valentyna A. Tymkova (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article deals with the simple sentence as a multidimensional unit of a non-verbal type of a sentence, formed in accordance with the semantic essence of predicates of quality. The results suggest that the sentence with divalent predicates of quality, in contrast to the sentence with monovalent predicates is characterized by asymmetry of correlations of their semantic and formally-grammatical structure. It has been noted that the theoretical basis for studyingthe propositional semantics of the sentence has been viewed in the works of Russian linguists: N.D. Arutiunova, V.V. Bohdanov, V. Kriuk, A.V. Paduchev, I.P. Sosov and others. It is typical for Russian linguistics that the parameters of sentences with predicates of quality are not clearly delineated due to the diverse nature of the criteria for allocating the predicates of quality into a separate semantic type of predicates. As we know, for the first time they were identified with the predicates of the action and status by L.V. Shcherba, in his classification the predicates of quality and predicates state do not overlap. Other linguists considered predicates of quality as state predicates at all. In Ukrainian syntax, only one integral concept of the semantic structure of the sentence is known, proposed by I.R. Vykhovanets. On its basis, the generalization of the phenomena of syntactic derivation, as well as the correlation of the semantic and formal-grammatical structure of various types of sentences has been conducted. On the basis of this generalized classification of predicates I.R. Vykhovanets has developed a more specific, six-component classification, in which the predicates of quality are allocated to a separate semantic class by their essential characteristics, which distinguish them from other types of predicates. Unlike the predicates of action, process and state, the predicates of quality attribute mean a constant, internal attribute, in a sense of an inseparable due to the subject. It has been mentioned that the characteristic peculiarity of the generative ability of predicates of quality is their typical combination with one unpredictable – the carrier of a qualitative feature. The unity of the valence framework is associated with the specifics of their semantics, primarily with the character of the attribute they express. The qualitative attribute of such predicates is a constant, internal attribute of creatures or objects, that is, it does not go beyond their limits. The semantic essence of most predicates of quality reveals only one valence position – the left-handed position of the carrier of a qualitative attribute, which in the semantic-syntactic tier of language is transformed into a substantive syntaxemus of the subject of a qualitative attribute. The bivalence of predicates of quality is classifies as an unusual phenomenon, acquired in connection with their consolidation in the predicate position of the sentence, because it contributed to their greater approximation to the typical predicate connectivity. Such predicates of quality for the expression of their attribute require the presence of another object. This means that in addition to the valence position of the unpredictable argument with the semantic function of the carrier of a qualitative attribute, they reveal another mandatory binding valence position – the position of not a predicate argument with the semantic function of the object. Consequently, as the central constituent of a semantically elementary sentence, the divalent predicate of quality acts in the context of two argument semantics – the carrier of a qualitative attribute and object. The object’s functions are different. It can be the object of comparison, when, by its attribute, the attribute of the carrier or the object of restriction is compared when it restricts the appearance of the attributes of the carrier. Such a semantic essence of divalent predicates of quality has led to corresponding specialized means of their expression – qualitative adjectives of the correlative attribute measure.